The insulin-degrading enzyme as a link between insulin and neuropeptides metabolism - Dorota Wacławczyk; Jerzy Silberring; Giuseppe Grasso (Taylor & Francis Group, 2021)
We have applied a recently developed HPLC-MS enzymatic assay to investigate the cryptic peptides generated by the action of the insulin-degrading enzyme (IDE) on some neuropeptides (NPs) involved in the development of tolerance and dependence to opioids. Particularly, the tested NPs are generated from the NPFF precursor (pro-NPFF (A)): NPFF (FLFQPQRF) and NPAF (AGEGLSSPFWSLAAPQRF). The results show that IDE is able to cleave NPFF and NPAF, generating specific cryptic peptides. As IDE is also responsible for the processing of many other peptides in the brain (amyloid beta protein among the others), we have also performed competitive degradation assays using mixtures of insulin and the above mentioned NPs. Data show that insulin is able to slow down the degradation of both NPs tested, whereas, surprisingly, NPAF is able to accelerate insulin degradation, hinting IDE as the possible link responsible of the mutual influence between insulin and NPs metabolism.